Unilateral distalization of a maxillary molar with sliding mechanics: A case report - (:unkn) unknown (My University, 2002)
Introduction: A unilateral Class II relationship could arise due to early loss of an upper second deciduous molar on one side during the mixed dentition period. This would allow the mesial drift of the molars, which may block the eruption of the second premolar. Methods and Results: A 15-year 8-month-old male patient presented with a Class II molar relationship on the right, and Class I canine and molar relationship on the left side. His E| was extracted when he was 5 years old. The 5 4| were impacted and the 3| was ectopically positioned due to the space loss from the mesial migration of the 7 6|. In addition 2 1|1 were in cross-bite. Skeletally he had Class III tendency with low MMPA. He presented with a straight profile and retruded upper lip. For maxillary molar distalization, a newly developed 'Keles Slider' was used. The appliance was composed of one premolar and two molar bands, and the anchorage unit was composed of a wide Nance button. |4 6 were connected to the Nance button and, therefore, included into the anchorage unit. The point of distal force application was close to the centre of resistance of the 6| and parallel to the occlusal plane. Ni-Ti coil springs were used and 200 g of distal force was applied. Seven months later the space required for eruption of the permanent premolars and canine was regained, and the anterior cross-bite corrected. The appliance was removed and final alignment of the teeth was achieved with fixed appliances. Conclusions: At the end of the second phase treatment Class I molar and canine relationship was achieved on the both sides, the anterior cross-bite was corrected, inter-incisal angle was improved, and ideal overbite and overjet relationship was achieved. The active treatment time was 27 months.
Keywords: Anchorage; Class II; Keles Slider; Molar distalization